ODR and the Public Order: Points of Contact - Pavel D. Konstantinov (Arbitrazh-Civil Procedure, 2026)
The current level of technological development of society makes it possible to transform existing traditional dispute resolution methods, creating new legal phenomena. These include online dispute resolution. It is noteworthy in this context that Russian law correlates these new legal phenomena of a technical nature with existing structures. Similar to how Chapter 31 of the Commercial Procedure Code of the Russian Federation applies to foreign decisions, foreign arbitral awards, recognition and enforcement of decisions rendered using ODR, are also included in this area of regulation. Accordingly, decisions made using the ODR are subject to the requirements of compliance with public policy as one of the key grounds for validity. The article examines both the traditional issues of the relationship between public order and alternative (including online) dispute resolution, as well as more specific aspects related to the discussion of models for overcoming state recognition and enforcement of decisions made using ODR.